1975
DOI: 10.1073/pnas.72.9.3290
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a protein matrix revealed by fluorescence quenching.

Abstract: ABSPIACT The fluorescence of the su posedly buried trtophan in ribonuclease T1 has been found to be collisionally quenched by acrylamide with a rate constant of 3 X 108 M-1 sec-1. Only a slight decrease in the quenching rate is observed upon a 5-fold increase in the viscosity of the solution. For this to be the case, the diffusion of the quencher must be limited by the protein matrix. To explain the process of diffusion through this complex material, the formation of "holes" in the lattice of a protein due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 19 publications
4
91
0
Order By: Relevance
“…The possibility that other small molecules might similarly enter proteins was raised by the work of Eftink & Ghiron (1975, who found that acrylamide (C 3 H 5 ON, molecular weight 71) could also quench the fluorescence of a variety of protein tryptophans. These investigators put forward the idea that the fluorescence-quenching capability of acrylamide could provide a 'kinetic ruler' that would gauge the relative accessibility of particular tryptophan residues to solvent.…”
Section: P+c^pc-^mentioning
confidence: 99%
“…The possibility that other small molecules might similarly enter proteins was raised by the work of Eftink & Ghiron (1975, who found that acrylamide (C 3 H 5 ON, molecular weight 71) could also quench the fluorescence of a variety of protein tryptophans. These investigators put forward the idea that the fluorescence-quenching capability of acrylamide could provide a 'kinetic ruler' that would gauge the relative accessibility of particular tryptophan residues to solvent.…”
Section: P+c^pc-^mentioning
confidence: 99%
“…The same technique has been used to demonstrate conformational mobility of apparently rigid residues in lysozyme (425), ribonuclease (426), and myoglobin (427). It has further been found that the fluorescence of a buried Trp in ribonuclease can be quenched by O2 (428,429), indicating that O2 can penetrate into the molecule. Similar results emerged from fluorescence relaxation (430), phosphorescence (431), and hydrogen exchange experiments (414).…”
Section: Thermal Fluctuations In Protein Structuresmentioning
confidence: 99%
“…Thermally induced conformational changes in BoNT/A light chain protein unfolding were also investigated by quenching of Trp fluorescence. The degree of exposure of Trp residues in solution as a function of temperature, monitored by fluorescence quenching technique, provides valuable information concerning the dynamics of protein folding (33). Acrylamide is an efficient quencher that preferentially quenches the more solvent-accessible Trp residues in multi-tryptophan proteins (34,35).…”
Section: Temperature-activated Endopeptidase Activity Of Bont/a Lightmentioning
confidence: 99%